REMEDIATION PRACTICES OF JUNIOR HIGH SCHOOL TEACHERS IN IMPROVING LEARNERS ACADEMIC PERFORMANCE UNDER THE MODULAR DISTANCE LEARNING MODALITY - Mirabueno, Verna; MONTEJO, JOY (International Journal of Arts, Sciences and Education, 2023)
ABSTRACT This study aimed to determine the Remediation Practices of Junior High School Teachers in Improving Learners Academic Performance under the Modular Distance Learning Modality. The schools covered by this study were the public secondary schools in the Division of Marinduque during the school year 2020-2021. There were 320 secondary school teachers who participated as the respondents of this study who were selected through random sampling technique. This is a descriptive research and utilized survey questionnaire in gathering data. The results from the data gathered revealed that the problem most of the student encountered is the lack of resources, while for the parent’s is lack of knowledge to academically guide their children as observed by the teachers. To address the problems of the learners, most teachers always give activities aligned with the MELC focusing on the least mastered skill of the students. In addition, the data gathered also indicates that most teachers did regular quarterly meetings with parents regarding the learner’s progress to address these difficulties. The data further shows that the most effective remediation practices in improving learners’ academic performance under the modular distance learning as perceived by the respondents is giving activities aligned with the MELC focusing on the Least Mastered Skill of the students.